ASSESSMENT OF QUALITY OF LIFE AND RELATED FACTORS IN ELDERLY PEOPLE WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE AT THE RESPIRATORY CLINIC, THONG NHAT HOSPITAL - Thị Điệp, Lê; Văn Quang, Hoàng; Thế Hoàng, Ngô; Duy Cường, Nguyễn; Thị Thanh Ngân, Huỳnh (Journal of Health and Aging, 2025)
To evaluate the quality of life and associated factors among elderly patients with COPD attending the Respiratory Outpatient Clinic, Thong Nhat Hospital. A cross-sectional study was conducted on 240 patients aged ≥60 years with confirmed COPD according to GOLD 2025 criteria. Clinical data were collected, and QoL was assessed using the validated Vietnamese version of the St. George’s Respiratory Questionnaire for COPD patients (SGRQ-C). Statistical analysis included descriptive statistics, bivariate tests, and multivariate logistic regression to identify independent factors associated with poor QoL. The mean age was 72 ± 8 years; 41.3% were 60–69 years, 41.3% were 70–79 years, and 40.8% were ≥80 years. Males accounted for 86.2%; 75.4% had a history of smoking, and 71.7% had at least one comorbidity. The mean total SGRQ-C score was 50.2 ± 19.6, with the symptoms domain being the most impaired (58.5 ± 19.5). Overall, 47.9% of patients had low or very low QoL. Multivariate analysis showed that age ≥70 (OR=1.7), female gender (OR=3.1), history of hospitalization, need for caregiver support (OR=1.2), GOLD group E (OR=1.2), and acute exacerbations requiring hospitalization (OR=1.3) were independently associated with poor QoL (p
Keywords: COPD; elderly; quality of life; SGRQ-C; Thong Nhat Hospital